Marriage and Materialism: Actor and Partner Effects Between Materialism, Importance of Marriage, and Marital Satisfaction - Ashley B LeBaron; David B Allsop; E. Jeffrey Hill; Brian J Willoughby; Sonya L. Britt-Lutter (Journal of Financial Therapy, 2017)
Drawing upon both the incompatibility of materialism and children model and marital paradigms theory, the purpose of the current study was to examine husband-wife actor and partner effects between materialism and marital satisfaction and to explore perception of the importance of marriage as a mediator of these relationships. Using a sample of 706 couples from the RELATE dataset, wives’ materialism negatively predicted both their own marital satisfaction as well as their husbands’ marital satisfaction. However, when controlling for financial problems in marriage, these effects became non-significant. Additionally, upon adding both wives’ and husbands’ importance of marriage (as well as combined couples’ “common fate” importance of marriage) to the model as mediators, indirect effects (actor and partner) between materialism and marital satisfaction were noted. Thus, when one partner (regardless of gender) places a high value on money and possessions, both spouses are less likely to place a high value on marriage, and are subsequently less likely to be satisfied in their marriage. Implications for financial therapists are discussed.
Keywords: materialism; marriage; financial therapy; marital satisfaction; marital importance; family finance